Signifikansi Pembatasan Waktu Penggunaan AC Terhadap Kenyamanan Termal - Wicaksono, Nugroho Budi; Arbiyanti, Pippie; Effendi, Sukma Meganova; Nugraha, Felix Krisna Aji; Widodo, Bernardinus Sri (ENERGI & KELISTRIKAN, 2024)
One of the Universal Apostolic Preferences (UAP): Caring for Our Common Home is in line with Pope Francis' encyclical letter: Laudato Si'. The encyclical also encourages academics to speak up about the environmental crisis to find better solutions before it is too late. The encyclical's mention of air-conditioning shows that we are not only worried about environmental issues, but also using energy in vain - for granted. In an effort to take care of our common home, this research seeks to implement the proposed time limitation of air conditioning use in the Department of Electromedical Technology, Faculty of Vocational Study, Sanata Dharma University, and evaluate the proposal based on primary data collected from the research. Data obtained from the electrical parameter monitoring system and temperature and humidity monitoring were used as primary data. The monitoring system utilizes ESP8266, PZEM-004T, and DHT22 hardware as internet of things (IoT) and data acquisition devices. The limitation of AC usage time showed a saving of 81,26 kWh from the monitoring results for 2 weeks, but thermal comfort with temperature limitation in the range of 28.7 ? - 31 ? was not met.